Beginning Python : from novice to professional - Hetland, Magnus Lie
Gain a fundamental understanding of Python's syntax and features with the third edition of Beginning Python, an up-to-date introduction and practical reference. Covering a wide array of Python-related programming topics, including addressing language internals, database integration, network programming, and web services, you'll be guided by sound development principles. Ten accompanying projects will ensure you can get your hands dirty in no time.Updated to reflect the latest in Python programming paradigms and several of the most crucial features found in latest Python 3. Advanced topics such as extending Python and packaging/distributing Python applications, are also covered.